A Regio‐ and Stereodivergent Synthesis of Homoallylic Amines by a One‐Pot Cooperative‐Catalysis‐Based Allylic Alkylation/Hofmann Rearrangement Strategy. Issue 31 (28th June 2019) - Pearson, Colin M.; Fyfe, James W. B.; Snaddon, Thomas N.
Abstract: Herein, we report a modular synthetic route to linear and branched homoallylic amines that operates through a sequential one‐pot Lewis base/transition‐metal catalyzed allylic alkylation/Hofmann rearrangement strategy. This protocol is operationally trivial, proceeds from simple and easily prepared substrates and catalysts, and enables all aspects of regio‐ and stereoselectivity to be controlled through a conserved experimental protocol. Overall, the high levels of enantio‐, regio‐, and diastereoselectivity obtained, in concert with the ability to access orthogonally protected or free amines, render this a straightforward and effective approach for the preparation of useful enantioenriched homoallylic amines. We have also demonstrated the utility of the products in the context of pharmaceutical synthesis. Abstract : Cooperation then amination : A unified one‐pot experimental procedure enables a versatile regio‐ and stereodivergent synthesis of homoallylic amines. Critical to the successful development of this method was the recognition that initial catalyzed C−C bond formation controls all aspects of regio‐ and stereoselectivity. Thereafter, in situ amination/Hofmann rearrangement results in stereospecific C−N bond formation.